Multifactorial analysis of factors influencing elite Australian football match outcomes: a machine learning approach - Fahey-Gilmour, J.; Dawson, B.; Peeling, P.; Heasman, J.; Rogalski, B. (International Journal of Computer Science in Sport, 2019)
In Australian football (AF), few studies have assessed combinations of pre- game factors and their relation to game outcomes (win/loss) in multivariable analyses. Further, previous research has mostly been confined to association-based linear approaches and post-game prediction, with limited assessment of predictive machine learning (ML) models in a pre-game setting. Therefore, our aim was to use ML techniques to predict game outcomes and produce a hierarchy of important (win/loss) variables. A total of 152 variables (79 absolute and 73 differentials) were used from the 2013-2018 Australian Football League (AFL) seasons. Various ML models were trained (cross-validation) on the 2013-2017 seasons with the-2018 season used as an independent test set. Model performance varied (66.5-73.3% test set accuracy), although the best model (glmnet - 73.3%) rivalled bookmaker predictions in the same period (70.9%). The glmnet model revealed measures of team quality (a player-based rating and a team-based) in their relative form as the most important variables for prediction. Models that contained in-built feature selection or could model non-linear relationships generally performed better. These findings show that AFL game outcomes can be predicted using ML methods and provide a hierarchy of predictors that maximize the chance of winning.